Application of short-term planning: case study in a construction site - Bergamo, Bruna; Catai, Rodrigo Eduardo (Brazilian Journal of Production Engineering, 2023)
According to the Brazilian Institute of Geography and Statistics (IBGE) statistics from 2021, civil construction represents an important fraction of the Brazilian economy. Although on the rise, the sector remained stagnant with regard to the management of resources, such as labor and materials, making the rate of waste, delays and cost of projects very high. Focusing on this issue, this research was carried out at a construction site in 2022, with the general objective of determining the relationship between short-term planning indicators and improvements in performance and productivity at the construction site. To obtain data, it was selected a construction site in the city of Curitiba that applies Last Planner tools, which encompasses short-term planning. In the work analyzed, a weekly diagnosis of the physical progress in relation to the plan was made, through the application and evaluation of indicators. By means of the indicators it was possible to verify that the enterprise presented delay in the completion of the planned activities, which was caused by the lack of commitment of the workforce. Thus, it could be concluded that the application of the short term contributes to obtaining information that helps  the progress of the schedule of construction.
Keywords: Planning; short term; Timeline